A super-high resolution frequency standard measuring approach based on phase coincidence characteristics between signals - 李智奇 周渭 陈发喜 刘晨光 (Chinese physics B, 2010)
A method for super high resolution comparison measurement is proposed in this paper with a comparison between the frequency standards of different nominal frequencies, which is based on phase coincidence detection of the two compared signals. It utilizes the regular phase shift characteristics between the signals. The resolution of the measurement approach can reach 10^-13/s at 5 MHz, and the self-calibration resolution can achieve 10^-14/s in the comparison between 10 MHz and 100 MHz, or even can reach 10^-15/s in the comparison between 10 MHz and 190 MHz. This method implies significant progress in the development of the high precision frequency standard comparison technology.